Isolation and Identification of Three New Sterigmatocystin Derivatives from the Fungus Aspergillus versicolor Guided by Molecular Networking Approach. Issue 6 (19th May 2020) - Han, Xiao; Tang, Xuli; Luo, Xiangchao; Sun, Caixia; Liu, Kechun; Zhang, Yun; Li, Pinglin; Li, Guoqiang
Abstract: Molecular networking approach was applied for the targeted isolation of new sterigmatocystin derivatives, sterigmatocystins A–C, from the marine sponge‐derived fungus Aspergillus versicolor . Sterigmatocystin A features a rare 6/6/6/6/5 polycyclic system. The structures of sterigmatocystins A–C, including absolute configurations, were determined on the basis of spectroscopic data and ECD calculations. Sterigmatocystin A showed more stronger promoting angiogenesis activity than the positive control at 1.25 μM level in transgenic fluorescent zebrafish. Sterigmatocystins A–C also exhibited moderate antiviral activity by the inhibition of HSV‐2. Abstract :